Impact of Emerging Technologies in Prenatal Genetic Counseling - Stevens, Blair (Cold Spring Harb Perspect Med, 2020)
For decades, prenatal testing has been offered to evaluate pregnancies for genetic conditions. In recent years, the number of testing options and range of testing capabilities has dramatically increased. Because of the risks associated with invasive diagnostic testing, research has focused on the detection of genetic conditions through screening technologies such as cell-free DNA. Screening for aneuploidy, copy number variants, and monogenic disorders is clinically available using a sample of maternal blood, but limited data exist on the accuracy of some of these testing options. Additional research is needed to examine the accuracy and utility of screening for increasingly rare conditions. As the breadth of prenatal genetic testing options continues to expand, patients, clinical providers, laboratories, and researchers need to find collaborative means to validate and introduce new testing technologies responsibly. Adequate validation of prenatal tests and effective integration of emerging technologies into prenatal care will become even more important once prenatal treatments for genetic conditions become available.